Comportamiento estudiantil y su influencia en el proceso académico de los estudiantes del décimo año de EGB de la Unidad Educativa Manuel Córdova Galarza, periodo lectivo 2022-2023 - Arias Jiménez, Carlos Manuel (2023)
The research entitled “Student behavior and its influence on the academic process of students in the tenth year of EGB of the Manuel Córdoba Galarza Educational Unit, school year 2022-2023” had as its main objective the establishment of the influence of student behavior in the institution and an analysis of the current situation in order to design a workshop for parents to improve the academic process of students. To achieve this, a methodology with a non-experimental design and a quantitative approach was carried out, with an applied, descriptive and explanatory type of research that allowed, through the data collection instrument of the 18-question survey, to obtain the opinion of 91 students regarding the problems addressed. As a result, the relationship between student behavior and the academic process was known, as well as the fact that the family also influences the behavior shown in the classroom. As a proposed solution, a series of eight workshops were proposed with topics such as: the development of social skills, values education, communication, conflict resolution, education without violence, the role of the family in the school, how to help student children and how to create study habits in their children, whose purpose was to improve the attitudes they show both at home and at school and thus their learning will be more effective.